Thermomechanics and infra-red imaging, volume 7 proceedings of the 2011 annual conference on experimental and applied mechanics - Proulx, Thomas A. (Conference proceedings of the society for experimental mechanics series, 2011)
Thermomechanics and Infra-Red Imaging represents one of eight volumes of technical papers presented at the Society for Experimental Mechanics Annual Conference & Exposition on Experimental and Applied Mechanics, held at Uncasville, Connecticut, June 13-16, 2011. The full set of proceedings also includes volumes on Dynamic Behavior of Materials, Mechanics of Biological Systems and Materials, Mechanics of Time-Dependent Materials and Processes in Conventional and Multifunctional Materials, MEMS and Nanotechnology; Optical Measurements, Modeling and, Metrology; Experimental and Applied Mechanics, and Engineering Applications of Residual Stress.